Current topics in developmental biology. - Schatten, Gerald (Current topics in developmental biology, 2003)
Together with other volumes in this series, Volume 58 presents thoughtful and forward-looking articles on developmental biology and developmental medicine. Reviews include: * A role for endogenous electric fields in wound healing * The role of mitotic checkpoint in maintaining genomic stability * The regulation of oocyte maturation * Stem cells: A promising source of pancreatic islets for transplantation in type 1 diabetes * Differentiation potential of adipose derived adult stem (ASAS) cells The exceptional reviews in this volume of Current Topics in Developmental Biology will be valuable to both clinical and fundamental researchers, as well as students and other professionals who want an introduction to current topics in cellular and molecular approaches to developmental biology and clinical problems of aberrant development. * Series Editor Gerald Schatten is one of the leading minds in reproductive and developmental science * Presents major issues and astonishing discoveries at the forefront of modern developmental biology and developmental medicine * The longest-running forum for contemporary issues in developmental biology with over 30 years of coverage.